AVALIAÇÃO DE ANTÍGENOS DE PARACOCCIDIOIDES BRASILIENSIS - Vicentini, A.P.; Oliveira, L.E.; Da Silva, D.F.; Zamboni, I.M.; Kloth, V.R.; Benad, G.; Assis, C.M. (Revista do Instituto Adolfo Lutz, 2002)
Ver PDF.